On types of degenerate critical points of real polynomial functions. (July 2020) - Guo, Feng; Phạm, Tiến-Sơn
Abstract: In this paper, we consider the problem of identifying the type (local minimizer, maximizer or saddle point) of a given isolated real critical point c, which is degenerate, of a multivariate polynomial function f . To this end, we introduce the definition of faithful radius of c by means of the curve of tangency of f . We show that the type of c can be determined by the global extrema of f over the Euclidean ball centered at c with a faithful radius. We propose algorithms to compute faithful radius of c and determine its type.